Application of SERS on the chemical speciation of individual Aitken mode particles after condensational growth. Issue 7 (2nd July 2020) - Kunihisa, Ryota; Iwata, Ayumi; Gen, Masao; Chan, Chak K.; Matsuki, Atsushi
Abstract: The chemical speciation of nanoparticles is technically challenging because of the minute mass of the particles. There is a constant need for more sensitive collection methods and chemical analyses. In this study, we demonstrated the applicability of a surface enhanced Raman scattering (SERS) technique on the rapid and sensitive chemical analysis of individual nanoparticles. SERS technique provides a significant enhancement of the scattering efficiency over traditional Raman spectroscopy. The novelty of the proposed technique is that the SERS substrate is used directly as the sampling substrate of a condensational growth tube (CGT) sampler, which can activate nanoparticles into water droplets and ensure simultaneous inertial sampling and SERS pretreatment. First, we investigated applicability of the method on mono-dispersed (20 nm, 50 nm, or 100 nm) ammonium sulfate (AS) and levoglucosan (LG) particles as model aerosols. The method was then applied to ambient nanoparticles. The successful detection of peaks corresponding to sulfate ν (SO4 2- ) and organics ν (C-H) indicates that our proposed method to combine a CGT sampler and SERS showed a sensitivity high enough to provide deep insights into the chemical speciation of atmospheric nanoparticles as small as 20 nm in diameter.